Electrospinning of a functional perfluorinated block copolymer as a powerful route for imparting superhydrophobicity and corrosion resistance to aluminum substrates - Grignard, Bruno; Vaillant, Alexandre; de Coninck, Joel; Piens, Marcel; Jonas, Alain M; Detrembleur, Christophe; Jerome, Christine (Langmuir, 2011)
Superhydrophobic aluminum surfaces with excellent corrosion resistance were successfully prepared by electrospinning of a novel fluorinated diblock copolymer solution. Micro- and nanostructuration of the diblock copolymer coating was obtained by electrospinning which proved to be an easy and cheap electrospinning technology to fabricate superhydrophobic coating. The diblock copolymer is made of poly(heptadecafluorodecylacrylate-co-acrylic acid) (PFDA-co-AA) random copolymer as the first block and polyacrylonitrile (PAN) as the second one. The fluorinated block promotes hydrophobicity to the surface by reducing the surface tension, while its carboxylic acid functions anchor the polymer film onto the aluminum surface after annealing at 130 °C. The PAN block of this copolymer insures the stability of the structuration of the surface during annealing, thanks to the infusible character of PAN. It is also demonstrated that the so-formed superhydrophobic coating shows good adhesion to aluminum surfaces, resulting in excellent corrosion resistance.